Tamiḻaka Antaṇar varalāṟu - Karuppaiyā (El. Kē. Em. Papḷikēṣaṉ, 2004)
On the history of Brahmans from Tamil Nadu.
Includes bibliographical references (p. [1012]-1023).
On the history of Brahmans from Tamil Nadu.
In Tamil; includes a chapter in English.
Keywords: Brahmans / India / Tamil Nadu / History.